The valve uptake index: improving assessment of prosthetic valve endocarditis and updating [18F]FDG PET/CT(A) imaging criteria . (6th January 2022) - Roque, Albert; Pizzi, María N; Fernández-Hidalgo, Nuria; Romero-Farina, Guillermo; Burcet, Gemma; Reyes-Juarez, José Luis; Espinet, Carina; Castell-Conesa, Joan; Escobar, Manuel; Ferreira-González, Ignacio; Aguadé-Bruix, Santiago; Cuellar-Calabria, Hug
Abstract: Aims: Diagnosis of prosthetic valve endocarditis (PVE) by positron emission computed tomography angiography (PET/CTA) is based on visual and quantitative morpho-metabolic features. However, the fluorodeoxyglucose (FDG) uptake pattern can be sometimes visually unclear and susceptible to subjectivity. This study aimed to validate a new parameter, the valve uptake index [VUI, maximum standardized uptake value (SUVmax)−mean standardized uptake value (SUVmean)/SUVmax], designed to provide a more objective indication of the distribution of metabolic activity. Secondly, to re-evaluate the utility of traditionally used PVE imaging criteria and determine the potential value of adding the VUI in the diagnostic algorithm of PVE. Methods and results: Retrospective analysis of 122 patients (135 prosthetic valves) admitted for suspicion of endocarditis, with a conclusive diagnosis of definite ( N = 57) or rejected ( N = 65) PVE, and who had undergone a cardiac PET/CTA scan as part of the diagnostic evaluation. We measured the VUI and recorded the SUVmax, SUVratio, uptake pattern, and the presence of endocarditis-related anatomic lesions. The VUI, SUVmax, and SUVratio values were 0.54 ± 0.1 vs. 0.36 ± 0.08, 7.68 ± 3.07 vs. 3.72 ± 1.11, and 4.28 ± 1.93 vs. 2.16 ± 0.95 in the 'definite' PVE group vs. the 'rejected' group, respectively (mean ± SD; P < 0.001). A cut-off value of VUI > 0.45 showed a sensitivity, specificity, and diagnostic accuracy for PVE of 85%, 88%, and 86.7% and increased diagnostic ability for confirming endocarditis when combined with the standard diagnostic criteria. Conclusions: The VUI demonstrated good diagnostic accuracy for PVE, even increasing the diagnostic power of the traditionally used morphometabolic parameters, which also confirmed their own diagnostic performance. More research is needed to assess whether the integration of the VUI into the PVE diagnostic algorithm may clarify doubtful cases and thus improve the diagnostic yield of PET/CTA. Graphical Abstract: